2013
DOI: 10.1158/0008-5472.can-12-3565
|View full text |Cite
|
Sign up to set email alerts
|

ATIP3, a Novel Prognostic Marker of Breast Cancer Patient Survival, Limits Cancer Cell Migration and Slows Metastatic Progression by Regulating Microtubule Dynamics

Abstract: Metastasis, a fatal complication of breast cancer, does not fully benefit from available therapies. In this study, we investigated whether ATIP3, the major product of 8p22 MTUS1 gene, may be a novel biomarker and therapeutic target for metastatic breast tumors. We show that ATIP3 is a prognostic marker for overall survival among patients with breast cancer. Notably, among metastatic tumors, low ATIP3 levels associate with decreased survival of the patients. By using a well-defined experimental mouse model of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 36 publications
7
78
0
Order By: Relevance
“…These results provided strong evidences indicating that MTUS1 was a potential tumor suppressor in gastric cancer. Our data are consistent with previous reports in breast cancer that silencing MTUS1 expression by siRNA facilitated breast cancer cell proliferation by accelerating cell cycle, and also promoted cell motility by regulating microtubule dynamics [27]. Further work will be conducted to illustrate if MTUS1 has a role in regulating tumor-associated angiogenesis or resistance to chemo-therapeutic drugs.…”
Section: Discussionsupporting
confidence: 91%
“…These results provided strong evidences indicating that MTUS1 was a potential tumor suppressor in gastric cancer. Our data are consistent with previous reports in breast cancer that silencing MTUS1 expression by siRNA facilitated breast cancer cell proliferation by accelerating cell cycle, and also promoted cell motility by regulating microtubule dynamics [27]. Further work will be conducted to illustrate if MTUS1 has a role in regulating tumor-associated angiogenesis or resistance to chemo-therapeutic drugs.…”
Section: Discussionsupporting
confidence: 91%
“…The expression or function of other microtubule regulators, such as survivin Rosa et al, 2006), ATIP3 (Molina et al, 2013;Velot et al, 2015) and the +TIPs EB1 (Liu et al, 2009;Stypula-Cyrus et al, 2014) and APC (Etienne-Manneville, 2009), was found to be altered in certain cancers, but the exact role of these proteins in 3D cell migration is still unclear. Mutations in genes encoding tubulin isoforms and different microtubule regulators including +TIPs have also been associated with neurodevelopmental diseases, including disorders of neuronal migration (Breuss and Keays, 2014;Chakraborti et al, 2016;van de Willige et al, 2016), and it will be interesting to investigate which of their functions reflect general mechanisms of 3D cell motility and which are neuron specific.…”
Section: Microtubule Alteration and Diseases Related To Cell Migrationmentioning
confidence: 99%
“…Moreover, expression of MTUS1 was significantly lower in triple-negative breast cancer (11). Silencing of MTUS1 expression promoted breast cancer cell proliferation, a result further supported in experiments using xenograft models (11,29). In colon cancer, Zuern et al found that silencing of MTUS1 significantly promoted cellular proliferation (12).…”
Section: Kaplan-meier Analysis For Cancer-specific (A) and Disease-mentioning
confidence: 81%